Evaluation in the Context of the Government Market Place: Implications for the Evaluation of Research - Connie K. Della-Piana; Gabriel M. Della-Piana (The Evaluation Center at Western Michigan University, 2007)
The evaluation community has concentrated on examining and explicating implications of the choice of methods for evaluating federal programs, as described in the New Directions for Evaluation edited by Julnes and Rog (2007), placing the policy debate in historical and contemporary contexts. In that volume and elsewhere we find that there are several mechanisms described for supporting and/or conducting program evaluation at the federal level. In the Julnes and Rog volume, Chelimsky (2007) describes evaluation activities conducted within the federal government by the Government Accountability Office (GAO). Both grants and contracts supported the work of Yin (Yin and Davis, 2007) in the evaluation of large comprehensive reforms in K-12 science and mathematics education. Other evaluation activities come under the authority of the Office of the Inspector General which conducts performance audits of government programs that draw on program evaluation and its methods (see the Yellow Book http://www.gao.gov/govaud/ybk01.htm).